Phytochemical content of traditional herbal medicines in South and Central Kalimantan - Fajar Lestari; Susy Andriani (Jurnal GALAM, 2021)
The use of medicine derived from natural ingredients had already begun since ancestors and passed down from generation to generation. However, the properties of those various plants were not clinically been proven. This study aims to find out phytochemical content of medicinal forest plants based on information from the local communities. The study was conducted in two ecosystem types namely wetland ecosystem in peat swamp of Sungai Rasau, Sebangau National Park, Central Kalimantan and dryland ecosystem in Meratus Mountain slope, Peramasan Bawah village, South Kalimantan. Vegetation data in the field was collected by making line transect. Phytochemical analyses qualitatively was done in the Faculty of Math and Natural Science laboratory of Lambung Mangkurat University, while specimen samples were taken from some species that commonly used by the local communities for medicinal purpose as 100 gr to 150 gr of gross weight of each plants. . Then the plant specimens were tested for their secondary metabolites comprised steroids/triterpenoids, quinone, tannin, flavonoids, saponins, and alkaloids tests in the laboratory. The research results showed that medicinal plants used by local communities were still available in their natural habitat In dryland ecosystem, there were 27 plant species discovered and 22 species found in peat swamp ecosystem that potentially use as herbal medicine. Phytochemical analyses showed that most of the plant samples were proved to have secondary metabolites in the form of steroid/triterpenoids, quinone, tannin, flavonoid, saponins and alkaloids. This condition showed that those plant species have potential as herbal medicine. However, those plant species still need further tests related to certain active ingredients potentially use as biopharmacy.Keywords: biopharmacy, peat, land, metabolite